-4m-13=3m+3-5m

Simple and best practice solution for -4m-13=3m+3-5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4m-13=3m+3-5m equation:


Simplifying
-4m + -13 = 3m + 3 + -5m

Reorder the terms:
-13 + -4m = 3m + 3 + -5m

Reorder the terms:
-13 + -4m = 3 + 3m + -5m

Combine like terms: 3m + -5m = -2m
-13 + -4m = 3 + -2m

Solving
-13 + -4m = 3 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
-13 + -4m + 2m = 3 + -2m + 2m

Combine like terms: -4m + 2m = -2m
-13 + -2m = 3 + -2m + 2m

Combine like terms: -2m + 2m = 0
-13 + -2m = 3 + 0
-13 + -2m = 3

Add '13' to each side of the equation.
-13 + 13 + -2m = 3 + 13

Combine like terms: -13 + 13 = 0
0 + -2m = 3 + 13
-2m = 3 + 13

Combine like terms: 3 + 13 = 16
-2m = 16

Divide each side by '-2'.
m = -8

Simplifying
m = -8

See similar equations:

| 16x^2+368x-2035=0 | | 3-8[3-(2y-9)]= | | -3.8+(-5.6)= | | 9÷3/5 | | 3.2=9 | | 15600=(200-10x)(90+5x) | | 5(v-6)=-2v+2 | | 2x+2y+2z=110 | | 35x=25+30x | | 33+8-x=180 | | 5(3-2)=-55 | | M-5=4m+13 | | 5(p+8)=85 | | -16.53=x-3.2 | | 7w-26=4(w-5) | | (9+u)(4u+1)=0 | | 7+3b=b+2+7+14 | | 8-5[8-(5y-4)]= | | 57+23+x=180 | | -8.1=x+3.3 | | 4x-7x-13=5 | | 36-2x=4x | | 17x=17x | | 2p+5q-8(2p-8q+9r)= | | 1/9*9-9 | | .7(n+6)=10 | | 3(x+13)-15=4x-8-9 | | 12a+6b-7a+8b= | | -n+6=-6-4n-3n | | 3x-10=56 | | 2=x+x^2 | | 1/9*-8-9 |

Equations solver categories